Vesicles Cytoplasmic Injection: An Efficient Technique to Produce Porcine Transgene‐Expressing Embryos. (3rd June 2016) - Luchetti, CG; Bevacqua, RJ; Lorenzo, MS; Tello, MF; Willis, M; Buemo, CP; Lombardo, DM; Salamone, DF
Contents: The use of vesicles co‐incubated with plasmids showed to improve the efficiency of cytoplasmic injection of transgenes in cattle. Here, this technique was tested as a simplified alternative for transgenes delivery in porcine zygotes. To this aim, cytoplasmic injection of the plasmid alone was compared to the injection with plasmids co‐incubated with vesicles both in diploid parthenogenic and IVF zygotes. The plasmid pcx‐egfp was injected circular (CP) at 3, 30 and 300 ng/μl and linear (LP) at 30 ng/μl. The experimental groups using parthenogenetic zygotes were as follows: CP naked at 3 ng/μl (N = 105), 30 ng/μl (N = 95) and 300 ng/μl (N = 65); Sham (N = 105); control not injected (N = 223); LP naked at 30 ng/μl (N = 78); LP vesicles (N = 115) and Sham vesicles (N = 59). For IVF zygotes: LP naked (N = 44) LP vesicles (N = 94), Sham (N = 59) and control (N = 79). Cleavage, blastocyst and GFP+ rates were analysed by Fisher's test (p < 0.05). The parthenogenic CP naked group showed lower cleavage respect to control (p < 0.05). The highest concentration of plasmids to allow development to blastocyst stage was 30 ng/μl. There were no differences in DNA fragmentation between groups. The parthenogenic LP naked group resulted in high GFP rates (46%) and also allowed the production of GFP blastocysts (33%). The cytoplasmic injection with LP vesicles into parthenogenic zygotes allowed 100% GFP blastocysts. Injected IVF showed higher cleavage rates than control (p < 0.05). In IVF zygotes, only the use of vesicles produced GFP blastocysts. The use of vesicles co‐incubated with plasmids improves the transgene expression efficiency for cytoplasmic injection in porcine zygotes and constitutes a simple technique for easy delivery of plasmids.